INTELEKTUAL ARENA PADA KKPK NEW BESTIES KARYA ORYZA SATIVA APRIYANI - Merpati, Rizky Dian (Jurnal Pena Indonesia, 2016)
Children's literature can be said that a literary work isinnya appropriate language and developmental age and the child's life, both written by authors who are already adults, adolescents or children themselves. The literary work is not only in the form of poetry and prose, but also the form of drama. This study examines the intellectual arena in the novel "New Besties work Oryza Sativa Apriyani". Data obtained by the intellectual arena in school and at home experienced by Dhilla figures. This study uses a sociological approach. This type of research is qualitative descriptive study. The technique used to collect data that is read engineering and technical notes.